Medicinal chemistry and biomedical applications of bismuth-based compounds and nanoparticles. (17th September 2021) - Griffith, Darren M.; Li, Hongyan; Werrett, Melissa V.; Andrews, Philip C.; Sun, Hongzhe
Abstract : Bismuth-based compounds have been used extensively as medicines for the treatment of gastrointestinal disorders and H. pylori infections. Bismuth compounds and Bi-based nanomaterials show promise for emerging infectious diseases, cancer ( e.g. 213 Bi) and also imaging. Abstract : Bismuth as a relatively non-toxic and inexpensive metal with exceptional properties has numerous biomedical applications. Bismuth-based compounds are used extensively as medicines for the treatment of gastrointestinal disorders including dyspepsia, gastric ulcers and H. pylori infections. Recently, its medicinal application was further extended to potential treatments of viral infection, multidrug resistant microbial infections, cancer and also imaging, drug delivery and biosensing. In this review we have highlighted the unique chemistry and biological chemistry of bismuth-209 as a prelude to sections covering the unique antibacterial activity of bismuth including a description of research undertaken to date to elucidate key molecular mechanisms of action against H. pylori, the development of novel compounds to treat infection from microbes beyond H. pylori and the significant role bismuth compounds can play as resistance breakers. Furthermore we have provided an account of the potential therapeutic application of bismuth-213 in targeted alpha therapy as well as a summary of the biomedical applications of bismuth-based nanoparticles and composites. Ultimately this review aims to provide the state of the art, highlight the untapped biomedical potential of bismuth and encourage original contributions to this exciting and important field.